Faktor-Faktor yang Mempengaruhi Penerapan Pendokumentasian Rekam Medis Elektronik (EMR) di Ruang internal RSUD Dr. R. Soedjono Selong - Indah Jamihaq Chaniago; Yessi Anggraini R; Erinna Rahmalia (Jurnal Pengetahuan dan Pendidikan, 2024)
The implementation of Electronic Medical Records (EMR) is a strategic step in modernizing healthcare services, aiming to improve documentation quality and service efficiency. This study aims to analyze the factors influencing the implementation of EMR documentation in the Internal Medicine Ward of Dr. R. Soedjono Selong Regional General Hospital. This study used a quantitative approach with a cross-sectional design and involved 33 respondents consisting of healthcare workers in the internal medicine ward. The research instrument was a questionnaire measuring demographic characteristics, computer literacy, computer facilities, knowledge, and attitudes toward EMR. The results showed that age, length of service, knowledge, and attitudes were significantly associated with EMR implementation, while gender, education, profession, computer literacy, and computer facilities showed no significant association. The most dominant factor influencing EMR implementation was healthcare workers' attitudes. These findings emphasize the importance of educational interventions and behavioral change in supporting the implementation of health information technology.